(untitled) (The International Journal of Educational Sciences and Arts, 2023)
This study aimed to investigate the effectiveness of a proposed model of a blended learning environment based on design thinking in developing motivation for achievement, and the researchers used the semi-experimental approach as a study methodology by employing design thinking in a blended learning environment and measuring its impact on developing motivation for achievement. The sample consisted of 60 students of the digital technology course 1-3 in the secondary stage, who were divided into two groups with 30 students in each. The study tool was a measure of motivation for achievement. The results of the study revealed that there are statistically significant differences between the experimental group and the control group in the post-measurement in favor of the experimental group. The study came with many recommendations, the most important is the need to integrate technological innovations into the educational process to keep pace with the requirements of the digital age, reorganize course content, and prepare educational tasks that suit the stages of design thinking to help students perform their tasks.